2012
DOI: 10.1155/2012/292730
|View full text |Cite
|
Sign up to set email alerts
|

In VivoClearance of Alpha-1 Acid Glycoprotein Is Influenced by the Extent of Its N-Linked Glycosylation and by Its Interaction with the Vessel Wall

Abstract: Alpha-1 acid glycoprotein (AGP) is a highly glycosylated plasma protein that exerts vasoprotective effects. We hypothesized that AGP’s N-linked glycans govern its rate of clearance from the circulation, and followed the disappearance of different forms of radiolabeled human AGP from the plasma of rabbits and mice. Enzymatic deglycosylation of human plasma-derived AGP (pdAGP) by Peptide: N-Glycosidase F yielded a mixture of differentially deglycosylated forms (PNGase-AGP), while the introduction of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The fast decrease in M5 can be explained by a second mechanism. M5 and in conclusion M5 containing glycoforms are probably removed by a specific clearance mechanism from circulation involving the mannose receptor which binds amongst others specifically to mannose containing glycoproteins and removes them from circulation with similar functions in humans and rabbits that were described previously ( 11 , 12 , 14 , 16 , 17 , 22 ). The incomplete removal of M5 from circulation observed in this study can be explained by the structural conformation of the Fc part.…”
Section: Discussionsupporting
confidence: 65%
“…The fast decrease in M5 can be explained by a second mechanism. M5 and in conclusion M5 containing glycoforms are probably removed by a specific clearance mechanism from circulation involving the mannose receptor which binds amongst others specifically to mannose containing glycoproteins and removes them from circulation with similar functions in humans and rabbits that were described previously ( 11 , 12 , 14 , 16 , 17 , 22 ). The incomplete removal of M5 from circulation observed in this study can be explained by the structural conformation of the Fc part.…”
Section: Discussionsupporting
confidence: 65%
“…Sialic acids influence plasma protein clearance and are directly involved in activation and control of the immune system. Moreover, their functions depend on the linkage type [22,37]. Our finding of increased sialylation in diabetes and with increasing BMI was specifically due to α2,6-sialylation, while α2,3-sialylation decreased.…”
Section: Sialylationmentioning
confidence: 62%
“…In addition, the results from a mice study indicated that systemic hyaluronidase treatment decreased the initial clearance of AGP and that AGP administration reduced the binding of hyaluromic acid binding protein to the vessel wall of liver sinusoids. [99] These results suggest that AGP, including N-linked glycans, interact with hyaluronan or hyaluronidase-sensitive component of the vessel wall which influence the transendothelial passage of AGP. Based on these results, a new hepatic elimination pathway involving at least two types of receptors, namely an asialoglycoprotein receptor and another yet to be identified receptor, for AGP was proposed ( Figure 5).…”
Section: Dispositionmentioning
confidence: 77%
“…[97] Pharmacoki-netic studies using mice and rabbits demonstrated that AGP was mainly distributed in the liver. [98,99] We also clarified that AGP was mainly incorporated into liver parenchymal cells via a receptor-mediated pathway, and the hemoglobin β-chain located on liver plasma membranes contributes to the intracellular uptake of AGP. [100,101] These data suggest that AGP is finally taken up by liver parenchymal cells via the hemoglobin β-chain and is then degraded or eliminated from the body.…”
Section: Dispositionmentioning
confidence: 89%
See 1 more Smart Citation